2022
DOI: 10.1371/journal.pone.0265436
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of self and its relationship with marital satisfaction and parenting styles in a Spanish sample of adolescents’ parents

Abstract: The present study aims to test some of the assumptions of Bowen’s Family Systems Theory, specifically, to assess the relationships between differentiation of self (DoS), marital satisfaction and parenting styles, as well as the gender differences in these variables in a Spanish sample. The sample includes 140 Spanish non-single adults, over 30 years old, who have at least one adolescent son or daughter, aged between 12 and 19 years old. The instruments used were a sociodemographic questionnaire, the Differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
(59 reference statements)
0
4
0
2
Order By: Relevance
“…Cavaiola et al (2012) también encontraron que los sujetos con mayor diferenciación del self y menor corte emocional tienen menos conflictos laborales con los superiores y con los compañeros. Por último, diversos estudios han hallado que las personas más diferenciadas tienen una mayor cohesión y flexibilidad familiar, un mayor ajuste marital, y una menor ansiedad y evitación en las relaciones de pareja, y que utilizan con sus hijos unos estilos educativos más inductivos y cálidos y menos indulgentes, autoritarios o críticos (Aryamanesh et al, 2012;Borondo y Oliver, 2021;Dolz-del-Castellar y Oliver, 2021;Lampis et al, 2017Lampis et al, , 2019Mozas-Alonso et al, 2022).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Cavaiola et al (2012) también encontraron que los sujetos con mayor diferenciación del self y menor corte emocional tienen menos conflictos laborales con los superiores y con los compañeros. Por último, diversos estudios han hallado que las personas más diferenciadas tienen una mayor cohesión y flexibilidad familiar, un mayor ajuste marital, y una menor ansiedad y evitación en las relaciones de pareja, y que utilizan con sus hijos unos estilos educativos más inductivos y cálidos y menos indulgentes, autoritarios o críticos (Aryamanesh et al, 2012;Borondo y Oliver, 2021;Dolz-del-Castellar y Oliver, 2021;Lampis et al, 2017Lampis et al, , 2019Mozas-Alonso et al, 2022).…”
Section: Discussionunclassified
“…Numerosos estudios han confirmado que las personas con mayor diferenciación tienen mejor salud física y mental (Lampis et al, 2019;Rodríguez-González et al, 2019), mejor regulación emocional y una menor ansiedad (Dolz-del-Castellar y Duch-Ceballos et al, 2020;Oliver et al, 2022), mayor autoestima menor evitación y ansiedad en las relaciones de apego adulto (Borondo y Oliver, 2021), y relaciones sociales, familiares y de pareja más funcionales (Aryamanesh et al, 2012;Dolz-del-Castellar y Oliver, 2021;Hainlen et al, 2016;Lampis et al, 2017Lampis et al, , 2019Likcani et al, 2017;Mozas-Alonso et al, 2022;Skowron et al, 2009).…”
unclassified
“…Numerous studies have delved into the interplay between DoS and romantic relationship satisfaction (e.g. 19 ). Peleg’s 20 study found an inverse correlation: lower emotional cutoff was linked to heightened romantic relationship satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…In today's world, the sanctity of the family nucleus is under threat, while marriage plays a fundamental role in the elevation and mental health of humans to the extent that many studies have shown that married individuals are healthier and happier (Mozas-Alonso et al, 2022;Wang & Zhao, 2023). The quality of the marital relationship forms a foundation that future family functioning and the physical and mental health of its members are built upon.…”
Section: Introductionmentioning
confidence: 99%
“…Marital satisfaction consists of objective feelings of happiness, satisfaction, and pleasure experienced by both spouses when considering all aspects of their marriage; recent studies on sanctity and the role of God in marriage show that for many people, belief in God affects their marital relationships in three areas: individual, relational, and spiritual. In the individual domain, people seek personal happiness and satisfaction, and marriage is a pathway through which individuals can achieve this (Mozas-Alonso et al, 2022;Nelson, 2022). It is important to note that the factors influencing satisfaction in marital relationships vary across cultures, with cultural effects being among the most significant factors affecting marital processes and outcomes, and receiving special attention from researchers.…”
Section: Introductionmentioning
confidence: 99%